2005
DOI: 10.1111/j.1365-313x.2005.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

A secreted lipase of Fusarium graminearum is a virulence factor required for infection of cereals

Abstract: SummaryFusarium graminearum is the causal agent of the Fusarium head blight (FHB) and a destructive pathogen of cereals accounting for high grain yield losses especially on wheat and maize. Like other fungal pathogens, F. graminearum secretes various extracellular enzymes, which are hypothesized to be involved in host infection. Extracellular lipolytic activity of F. graminearum was strongly induced in culture by wheat germ oil; this allowed us to isolate, clone, and characterize a gene (FGL1) encoding a secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
232
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(243 citation statements)
references
References 65 publications
10
232
0
1
Order By: Relevance
“…Similar results were recently reported for the corresponding Botrytis lipase gene on its host plant bean (Reis et al, 2005). In contrast, the F. graminearum gene FGL1, encoding a 35 kDa putative secreted lipase, belonging to a Rhizomucor miehei lipase family (Schmidt-Dannert, 1999), is required for virulence of F. graminearum on wheat and maize (Nasser Eddine et al, 2001;Voigt et al, 2005).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results were recently reported for the corresponding Botrytis lipase gene on its host plant bean (Reis et al, 2005). In contrast, the F. graminearum gene FGL1, encoding a 35 kDa putative secreted lipase, belonging to a Rhizomucor miehei lipase family (Schmidt-Dannert, 1999), is required for virulence of F. graminearum on wheat and maize (Nasser Eddine et al, 2001;Voigt et al, 2005).…”
Section: Discussionsupporting
confidence: 70%
“…The expression of both genes is induced in vitro by WGO and suppressed by sucrose or glucose. In contrast, no FGL1 transcripts were detected in fungal culture incubated in water (Voigt et al, 2005), whereas expression of LIP1 was significantly induced when the fungus was cultured in sugar-deficient minimal medium (data not shown). These results suggested that overlapping, but distinct regulatory mechanisms are involved in induction of LIP1 and FGL1 gene expression.…”
Section: Discussionmentioning
confidence: 67%
“…14, 15 Comparing the infection process in wild-type-and Δfgl1-infected wheat spikes with microscopic and biochemical methods, we were able to unravel the role of FGL1 in F. graminearum virulence. Analysis of the free fatty acid (FFA) content of infected spikelet tissue revealed that the secreted lipase FGL1 is required to release relatively high amounts of the polyunsaturated FFAs linoleic Keywords: (1,3)-β-glucan, cereal pathogen, Fusarium graminearum, plant defense, Triticum aestivum the fungal pathogen Fusarium graminearum is the causal agent of Fusarium head blight (FhB); a devastating crop disease resulting in heavy yield losses and grain contamination with mycotoxins.…”
mentioning
confidence: 95%
“…The GZEL lipase has been demonstrated to act as a virulence factor and is important to the pathogenicity of F. graminearum (G. zeae; Voigt et al, 2005). It has been suggested that inhibition of the lipase by ebelactone B (a known lipase inhibitor) might reduce the severity of the disease (Voigt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that inhibition of the lipase by ebelactone B (a known lipase inhibitor) might reduce the severity of the disease (Voigt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%